Configuring Urban Carbon Governance: Insights from Sydney, Australia. Issue 1 (2nd January 2016) - McGuirk, Pauline M.; Bulkeley, Harriet; Dowling, Robyn
Abstract : In the political geography of responses to climate change, and the governance of carbon more specifically, the urban has emerged as a strategic site. Although it is recognized that urban carbon governance occurs through diverse programs and projects—involving multiple actors and working through multiple sites, mechanisms, objects, and subjects—surprisingly little attention has been paid to the actual processes through which these diverse elements are drawn together and held together in the exercise of governing. These processes—termed configuration —remain underspecified. This article explores urban carbon governance interventions as relational configurations, excavating how their diverse elements—human, institutional, representational, and material—are assembled, drawn into relation, and held together in the exercise of governing. Through an analysis of two contrasting case studies of urban carbon governance interventions in Sydney, Australia, we draw out common processes of configuring and specific sets of devices and techniques that gather, align, and maintain the relations between actors and elements that constitute intervention projects. We conclude by reflecting on the implications of conceiving of governing projects as relational configurations for how we understand the nature and practice of urban carbon governance, especially by revealing the diverse modes of power at work within processes of configuring.